Eliminação de resistência a drogas por cádmio em Pseudomonas aeruginosa e descoloração do preto de remozol por co-metabolismo - Vilar Junior, Jose Carlos (2012)
Pseudomonas aeruginosa is an opportunistic pathogen microorganism was considered one of the most important agents of nosocomial infections due to its multiple resistance to many existing antibiotics. It is found in soil, water, plants, animals, food and various hospital settings, due to its high potential for resistance can perform processes of bioremediation. One of the biggest environmental problems generated in the activities of a textile industry is the large number of highly polluting effluents generated among the pollutants out to the black dye Remazol, which has caused serious environmental problems such as transparency and affect the aesthetics of water bodies thus preventing the penetration of sunlight, and thus the photosynthetic activity. In this regard, initial studies were performed with P. aeruginosa (UCP1567) isolated from hospital environment through the elimination of plasmids related to antibiotic resistance, using cadmium. The sample was acclimatized twice in Luria Bertani medium containing glucose, through the Minimum Inhibitory Concentration determined for cadmium (32μg/mL and 52 mg / mL, respectively) using the dilution method. The results suggest that heavy metal was effective in eliminating the resistance plasmids, corresponding to 84.61% for acclimation to cadmium 32μg/mL, and 92.30% for 52 mg / mL. Then, after eliminating the culture of resistance by cadmium, was submitted to the decolorization of Remazol black through a 23 factorial design, with independent variables agitation, the dye concentration and inoculum size, and as the response variable discoloration of the dye. The results showed that the potential for bioremediation of P. aeruginosa was not affected, and that culture after removal of microbial resistance, caused a discoloration of 85 to 94.4% of the dye, under conditions of rest, and 52% and agitation of 100 rpm and 45% under agitation at 200 rpm.